Potensi Es Krim Klorofil Daun Suji (Plomele angustifolia) sebagai Pangan Fungsional - Nugraheni, Oktina; Mustofa, Akhmad; Jokopriyambodo, Wahyu; Puyanda, Irvia Resti (UHAMKA PRESS, 2025)
Ice cream is one of the dairy products favored by all because of its sweet and delicious taste for dessert. Suji leaves are plants that are spread in Indonesia, chlorophyll in suji leaves can be used as a natural colorant and source of antioxidants. The purpose of this study was to determine the physical and chemical properties of ice cream with the addition of suji leaf chlorophyll extract. This study used a completely randomized design (CRD) with 2 factors, namely the first factor of adding chlorophyll extract (A1 = 0.1%, A2 = 0.15%, A3 = 0.2%) of suji leaves and the second factor of adding full cream milk powder with various brands (B1, B2, and B3). The parameters measured were overrun, melting speed, color, total sugar, soluble protein, total fat, antioxidant activity, and total chlorophyll. The results showed that the best formulation based on the highest antioxidant activity was A2B3 formulation with antioxidant activity of 52.61%, total fat 6.71%, soluble protein 37.96 mg BSA/ml, total sugar 1,649.76 mg glucose/ml, total chlorophyll 0.93 mg/L, color (L*: 71.84; a*: -8.54; b*: 9.80), overrun 13.48%, and melting speed 16 minutes. Ice cream with the addition of suji leaf chlorophyll extract has a potential as functional food